The effectiveness of the Ethics Quarter intervention on the ethical activity profile of nurse managers: A randomized controlled trial - Laukkanen Laura; Suhonen Riitta; Poikkeus Tarja; Löyttyniemi Eliisa; Leino-Kilpi Helena (Wiley, 2022)
Aim: To test the effectiveness of a new ethics educational e-learning intervention, Ethics Quarter, in supporting nurse managers' ethical activity profile.
Background: Health care organisations need evidence-based ethics interventions to support nurse managers' ethical activity profile.
Methods: A parallel-group, individually randomized controlled trial was conducted in 2020. Finnish nurse managers nationwide [members of the Union of Health and Social Care Professionals in Finland (Tehy) trade union] were randomly allocated to intervention (n = 169) or control group (n = 172). The intervention group participated in the Ethics Quarter comprising twelve 15-min evidence-based educational 'quarters' spread over 6 weeks. The control group had standard organisational ethics structures. The primary and secondary outcomes were ethical activity profile and ethics knowledge, respectively. The Consolidated Standards of Reporting Trials (CONSORT) statement for study design and reporting was adopted.
Results: Ethical activity profile showed statistically significant differences in mean changes between the groups from baseline to 10 weeks: all five dimensions were statistically significantly higher in the intervention group compared with the control group (p = <.0001).
Conclusion: The Ethics Quarter was effective in increasing nurse managers' ethical activity profile. Implications for Nursing Management Applying this ethics educational e-learning intervention would benefit nursing management education and health care organisations. Trial Registration : NCT04234503.